Rapid and sensitive colorimetric method for visualizing biotin-labeled DNA probes hybridized to DNA or RNA immobilized on nitrocellulose: Bio-blots. - Leary, J J (Proc Natl Acad Sci U S A, 1983)
Biotin-labelled DNA probes, prepared by nick-translation in the presence of biotinylated analogs of TTP, are hybridized to DNA or RNA immobilized on nitrocellulose filters. After removal of residual probe, the filters are incubated for 2--5 min with a preformed complex made with avidin-DH (or streptavidin) and biotinylated polymers of intestinal alkaline phosphatase. The filters are then incubated with a mixture of 5-bromo-4-chloro-3-indolyl phosphate and nitro blue tetrazolium, which results in the deposition of a purple precipitate at the sites of hybridization. This procedure will detect target sequences in the 1- to 10-pg range after enzyme incubation periods of 1 hr or less. The incubation period can be extended up to 24 hr, if required, to increase the color intensity of the hybridization signal. Furthermore, at high probe concentrations (250--7560 ng/ml), biotin-labeled DNA exhibits lower nonspecific binding to nitrocellulose than does radiolabeled DNA, so hybridization times required for the analysis of unique mammalian gene sequences can be decreased to 1--2 hr. This nonradiographic method of probe detection should be of general utility for genetic studies using Southern, RNA, or dot-blot hybridization protocols. IMAGES: